Cultural Efforts to Maintain Environmental Sustainability: A Study of the Pragmatics of Politeness on Ethical Planks in Rural Sunda - Riza Lupi Ardiati (Publindo Akademika, 2022)
This study examines politeness utterances implemented with manaa kanban (ethics plank) in Sundanese society. In Japanese culture, this method is intended as a medium for giving specific directions and instructions. In the context of this research, the Kanban method has a pragmatic goal of motivating people to care about cleanliness and natural beauty. It is also an effort to regenerate Sundanese politeness discourses as a way of life for the people of West Java, which has always been instilled and contains noble values. Methods The research was conducted through field observations, searching for data from respondents using taping techniques. The theory used is pragmatics related to the principle of politeness, the relationship between speakers and their speech, as well as soft Japanese expressions (kanwa hyougen). This research was conducted in Sayang village, Subang, West Java. The results of the study revealed that in some places, there were no garbage disposal facilities, and there were trees that were used as promotional media for certain interests.